234k views
2 votes
What is the answer too x^2+2x-59=3x-3

User Gkalpak
by
4.7k points

2 Answers

3 votes

Answer:

Explanation:

x^2 + 2x - 59 = 3x - 3

x^2 + 2x - 3x -59 +3 = 0

x^2 - x - 56 = 0

x^2 - (8 - 7)x - 56 = 0

x^2 - 8x + 7x - 56 = 0

x(x - 8) + 7(x - 8) = 0

(x + 7)(x - 8) = 0

either (x + 7) = 0

Or, (x - 8) = 0

x + 7 = 0

x = 0 - 7

x = -7

x - 8 = 0

x = 0 + 8

x = 8

therefore x = -7 , 8

User Singularhum
by
4.3k points
2 votes
Here, try this, I’m not sure though.
What is the answer too x^2+2x-59=3x-3-example-1
User Gibryon Bhojraj
by
4.6k points